KAJIAN TEMATIS TENTANG LARANGAN PEREMPUAN HAID MASUK MESJID DAN MEMBACA AL-QUR’AN - Elfia Elfia (AGENDA: Jurnal Analisis Gender dan Agama, 2019)
The research’s aim is to present a thematic study of the prohibition of menstruating women to come inside the mosque and recite Al Qur’an. It is based on certain hadith with various Islamic histories.  The analysis of mufradat and the content of hadith are used to reveal its prohibition. The method used in this research was library research or documents with a Maudhu'iy (thematic) approach. The results of this research concluded that menstruating women and Junub people are not forbidden to come inside the mosque for any reasons as long as they can keep their menstrual blood was not scattered in the mosque. It was based on several hadith proposed by Ibn Hazm and Aisyah. The reasons given by Ibn Hazm are relevant to the conditions of the present age. While reciting al-Qur'an, there is no single valid hadith stated by Imam al-Bukhari. It can be assumed that menstruating women may recite Al Qur'an. If they are forbidden to recite Al Qur'an and do dhikr, then she will be far from Allah as quoted in the hadith from Aisyah as explained that the prophet will always remember Allah all times